PERBANDINGAN METODE LATIHAN SMALL SIDED GAMES DENGAN ATURAN ONE TOUCH, TWO TOUCH, DAN FREE TOUCH TERHADAP KEMAMPUAN DECISION MAKING DAN SKILL EXECUTION DALAM PERMAINAN SEPAKBOLA DI USIA MUDA - Bangkit Pramudya Putra, Bangkit (2021)
The purpose of this study was to find out the Small Sided Games training method on soccer playing skills, especially Decision Making and Skill Execution in the young SSB environment. This research is about "Comparison of Small Sided Games Training Methods with One Touch, Two Touch, and No Touch rules on Decision Making Skills and Skill Execution in the game of football at a young age". The research method used is an experimental method with a total sampling technique, namely 16 students of SSB PAMONG PRAJA KU-13 Years. The research instrument used was the GPAI test (Game Performance Assessment Instrument). Meanwhile, to find out the difference in the increase in the results of the sample exercise using SPSS version 25 testing on the two results. There is a significant effect of Small Sided Games practice with One Touch, Two Touch rules on Decision Making and Skill Execution playing skills at a young age, There is a significant effect of Small Sided Games Free Touch practice on Decision Making and Skill Execution playing skills at a young age . and there is no significant effect of the Small Sided Games one touch, two touch and free touch training on decision-making football playing skills. It is recommended to coaches, teachers, football training and readers to provide Small Sided Games Two Touch training in order to improve football passing skills in the implementation of training programs for soccer athletes in the 13-year-old group.